Variable–focus liquid lens simulation. (1st January 2015) - Ghazian, Osameh; Sabarinathan, Jayshri
A numerical study of liquid–based variable lenses is presented in this paper. The effect of applied voltage and the contact angle of the surface are taken into account. The conservation of mass and the Navier–Stokes equations for a Newtonian incompressible fluid were solved to model the fluid flow both inside and outside the droplet. The electrohydrodynamic equations have been solved using the commercial software COMSOL MULTIPHYSICS™ based on the finite element method. It was found that by increasing the viscosity ratio, the time response decreases which can be suitable for camera purposes.